Case Report: A Chinese child with Barth syndrome caused by a novel TAFAZZIN mutation - Che, Mingxuan; Li, Fuhai; Jia, Yaning; Liu, Qingzheng; Hu, Jian; Zhang, Jidong; Liu, Shiguo (Frontiers in Cardiovascular Medicine, 2024)
Barth syndrome (BTHS) is a rare X-linked recessive genetic disorder characterized by a broad spectrum of clinical features including cardiomyopathy, skeletal myopathy, neutropenia, growth delay, and 3-methylglutaconic aciduria. This disease is caused by loss-of-function mutations in the TAFAZZIN gene located on chromosome Xq28, resulting in cardiolipin deficiency. Most patients are diagnosed in childhood, and the mortality rate is highest in the early years. We report a case of acute, life-threatening metabolic decompensation occurring one day after birth. A novel TAFAZZIN splice site mutation was identified in the patient, marking the first reported case of such a mutation in BTHS identified in China. The report aims to expand our understanding of the spectrum of TAFAZZIN mutations in BTHS.